WHY DO PEOPLE TRAVEL TO INLAND WATER RESORTS AND HOW DO THEY SELECT THEIR DESTINATION? DO AGE AND TRAVEL COMPANIONSHIP MATTER? - István EGRESI; Bianca Sorina POP-RĂCĂŞAN (Oradea Journal of Business and Economics, 2025)
his study explores the demographic profile, motivations, and preferences of visitors to Băile Figa, an inland water resort in Northwestern Romania. Data were collected using a convenience sampling method. The 200 questionnaires gathered were subsequently processed and analyzed using SPSS 26, a statistical software designed for social sciences. The majority of respondents were male, under 45 years old, with lower education levels and incomes. Most were repeat visitors, staying for at least two days and spending over 100 lei daily, primarily traveling by car with family or friends. The study found that key motivations for visiting included relaxation, swimming, sunbathing, and socializing, while medical treatment and boredom were cited less frequently. The resort’s freshwater pools, affordable entry fees, and natural surroundings were identified as the most appealing features, whereas proximity to home and therapeutic facilities had a lesser influence on visitors’ decisions. Băile Figa attracts a diverse audience, but motivations vary significantly by age and travel group: younger visitors (aged 18–29) prioritized socializing with friends, while older visitors were more motivated by health benefits, therapeutic facilities, and proximity to home. Family travelers valued the resort’s scenic environment and therapeutic offerings, whereas those traveling with friends showed less interest in these aspects. These findings underscore the importance of tailoring marketing strategies to different demographic segments. For younger visitors, campaigns should emphasize leisure and affordability, while for older and family-oriented tourists, the focus should be on health benefits and therapeutic offerings. By addressing the distinct preferences of each group, Băile Figa can enhance its appeal and better meet the needs of its diverse visitor base.